2013
DOI: 10.1002/jnr.23226
|View full text |Cite
|
Sign up to set email alerts
|

Acute inflammation alters adult hippocampal neurogenesis in a multiple sclerosis mouse model

Abstract: Neural precursor cells (NPCs) located in the subgranular zone (SGZ) of the dentate gyrus (DG) give rise to thousands of new cells every day, mainly hippocampal neurons, which are integrated into existing neuronal circuits. Aging and chronic degenerative disorders have been shown to impair hippocampal neurogenesis, but the consequence of inflammation is somewhat controversial. The present study demonstrates that the inflammatory environment prevailing in the brain of experimental autoimmune encephalomyelitis (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 45 publications
5
21
0
Order By: Relevance
“…Huehnchen et al observed an increase of proliferating NPC in EAE, that however did not result in an increase of mature NeuN positive neurons in the DG [15]. Similar to our results, Giannakopoulou et al could not demonstrate any significant changes in the number of NPC, however, they reported an increase of newborn radial-glia-like progenitor cells [16]. Taking into account the complex nature of autoimmune CNS inflammation, it is likely that different immune mechanisms and their heterogeneous spatial and temporal appearance have divergent effects on neurogenesis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Huehnchen et al observed an increase of proliferating NPC in EAE, that however did not result in an increase of mature NeuN positive neurons in the DG [15]. Similar to our results, Giannakopoulou et al could not demonstrate any significant changes in the number of NPC, however, they reported an increase of newborn radial-glia-like progenitor cells [16]. Taking into account the complex nature of autoimmune CNS inflammation, it is likely that different immune mechanisms and their heterogeneous spatial and temporal appearance have divergent effects on neurogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…While stimulation of the innate immune systems seems to inhibit neurogenesis [9], others have reported that myelin-specific T cells foster oligodendrogenesis [10] and neurogenesis [11]. Differences in experimental models, immunization protocols and investigated time points are likely at the origin of discrepancies in recent studies investigating adult neurogenesis during EAE [1216]. …”
Section: Introductionmentioning
confidence: 99%
“…This was not surprising, because hippocampus neurogenesis is a plastic event regulated, among many other factors, by sex steroid hormones (Barha et al, 2011;Gould, 2007;Brinton et al, 2008) and neuroinflammation. Regarding the latter, changes of cell proliferation coupled to reduced newborn cell maturation have been found in mice with neuroinflammation due to acute onset EAE (Pluchino et al, 2008;Guo et al, 2010;Huehnchen et al, 2011;Giannakopoulou et al, 2013). In chronic EAE, as reported in our current investigation, vehicle-treated EAE mice showed slightly improved number of Ki67 + proliferating cells and DCX + neuroblasts.…”
Section: Discussionsupporting
confidence: 56%
“…Memory, cognition and learning are key hippocampal functions linked to dentate gyrus neurogenesis (Kempermann, 2002;Gould, 2007;Galea et al, 2006). In this regard, neurodegenerative changes and altered neurogenesis have been discovered in EAE mice, including a decrease in CA1 pyramidal layer volume, reduction of cell proliferation (Pluchino et al, 2008;Guo et al, 2010;Ziehn et al, 2010), or enhanced cell proliferation but reduced capacity to generate neuroblasts and mature neurons (Giannakopoulou et al, 2013;Huehnchen et al, 2011). These reports have studied animals in the acute phase of EAE or 20 days afterwards.…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that cognitive dysfunction is correlated with hippocampal demyelination (157). Although the molecular mechanisms that control hippocampal NSC proliferation and differentiation in physiology and pathological conditions are unknown, recent findings reveal that acute inflammatory demyelination in animal model of MS could provoke the hippocampal stem cell niche and enhance proliferation of NPCs in SGZ (158). Thus, inflammatory factors such as cytokines and chemokines can affect the proliferative capacity of NSCs and alter neurogenesis in the SGZ (159).…”
Section: Sgz Of the Hippocampusmentioning
confidence: 99%